Vaginal discharge: Its causes and associated symptoms as perceived by rural north Indian women - Singh A (Wolters Kluwer Medknow Publications, 2007)
Background : Reproductive health is closely associated with culture of a country. Its sign and symptoms can be best understood within the ethnomedical contest rather then biomedical theories. Objective : To ascertain the views of the respondents regarding vaginal discharge. Methods : Three roadside villages of Panchkula, Haryana was purposively selected. A house to house survey was done and a total of 236 married women 15-45 years were interviewed by a female social worker on various aspect on vaginal discharge. Six FGDs and five case studies were also done. Results: Prevalence of vaginal discharge was 28.7%. Weakness, backache and poor vision were told as the main health effects of vaginal discharge. Heat, melting of bones, sexual promiscuity, poor hygiene and diet were told as the major causes of vaginal discharge. Consultation rate for vaginal discharge was 59%. Conclusion: The views of the rural north Indian women regarding vaginal discharge reflected the Ayurvedic system of thinking of the Indian masses.